Tertúlias Dialógicas Pedagógicas na formação docente: prevenção de violência sexual contra crianças e adolescentes. - Rodrigues, Rafaela Maria (Universidade Federal de São Carlos, 2023)
Sexual violence against children and adolescents has increasingly alarming rates in Brazil and worldwide. The school has been pointed out in international and national studies as a fundamental institution to combat and prevent violence, and teacher training as a still fragile element to make this happen. Focusing on the dialogical perspective of teacher training on the theme, around the reading and dialog of scientific articles on the subject, the objective of this research is to analyze the limits and possibilities of a continuing education course with these characteristics. The research question that guided us is: How can the Pedagogical Dialogical Training, carried out through a continuing education course, organized based on Dialogic Pedagogical Gatherings of scientific texts about the prevention of sexual violence against children and adolescents, act on the conceptions of the teachers participating in it and the engagement in their professional practice on the theme? The research methodology was qualitative, with data collection through questionnaire, observation, and focus group, with a communicative approach. In the dissertation qualification document the analyses have not yet been carried out. The analyses produced the following categories: Guardianship Council, Formation and training of teachers, Dialogic Gatherings, Valiant Club, Support and protection networks, Course development, Sanderson's book, Family and sexual education. As results, by means of the excluding and transforming elements, we concluded as main results, that the course produced in the teachers involved deep knowledge about the theme of prevention of child sexual abuse. Through the categories, we ascertained that greater unity is needed between the school and the Guardianship Council for the effective protection of children and adolescents; the Dialogic Gatherings and the Valiant Club are evidence-based actions for the prevention of violence; and it is urgent to train education professionals on the prevention of child sexual violence.
Dialogic Pedagogical Gatherings in teacher training: prevention of sexual violence against children and adolescents
Tertulias Pedagógicas Dialógicas en la formación del profesorado: prevención de la violencia sexual contra niños y adolescentes
Keywords: Prevenção; Violência sexual; Crianças; Formação docente; Tertúlias Dialógicas Pedagógicas; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO